The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/infdis/jit134
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immunity to Plasmodium falciparum Merozoite Surface Protein 1 and Protection From Infection With Blood-Stage Parasites

Abstract: Evaluating combined allele-specific cellular and humoral immunity elicited by malaria provides a more informative measure of protection relative to evaluation of either measure alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
1
33
1
1
Order By: Relevance
“…Several studies carried out in low-, medium-, and high-transmission areas have measured the time required for Plasmodium parasites to reappear in the blood of individuals after parasitemia has been cleared with blood-stagespecific antimalarial compounds (14,15,21,30,(44)(45)(46)(47). Interestingly, these and other modeling studies have revealed a discrepancy between the estimated number of infective bites per human per time unit (i.e., the EIR) and the resulting force of infection (FOI; i.e., the rate of new blood-stage infections) (16,33).…”
Section: Induction Of Type I Ifn and Ifn-␥ By A First P Berghei Livementioning
confidence: 99%
“…Several studies carried out in low-, medium-, and high-transmission areas have measured the time required for Plasmodium parasites to reappear in the blood of individuals after parasitemia has been cleared with blood-stagespecific antimalarial compounds (14,15,21,30,(44)(45)(46)(47). Interestingly, these and other modeling studies have revealed a discrepancy between the estimated number of infective bites per human per time unit (i.e., the EIR) and the resulting force of infection (FOI; i.e., the rate of new blood-stage infections) (16,33).…”
Section: Induction Of Type I Ifn and Ifn-␥ By A First P Berghei Livementioning
confidence: 99%
“…These cytokines facilitate immune priming and can influence whether the immune response promotes the onset of immunity or assists immune escape. DC-generated IL-12 can drive T cell IFN-␥ secretion and promote cytotoxic capacity (15), as well as facilitate the development of clinical immunity to malaria (16)(17)(18)(19). TNF can promote the maturation and survival of DCs in vitro (20,21), but in circulating blood TNF is not sufficient for maturation of CD1c ϩ mDCs (9).…”
mentioning
confidence: 99%
“…Research suggests a protective effect both for antibodies (18)(19)(20)(21) and effector T cell cytokine responses (particularly gamma interferon [IFN-␥]) (21)(22)(23)(24). As the induction and maintenance of both effective B cell (antibody) and T cell (cytokine) responses require functional DC (25) and each may be modulated by Treg cells (26), we sought to examine these cells in both children and adults with patent asymptomatic P. falciparum or P. vivax infection and to compare their responses to those seen with acute uncomplicated P. falciparum or P. vivax malaria.…”
mentioning
confidence: 99%